CyTOF Mass Cytometry for Click Proliferation Assays. Issue 1 (5th July 2017) - Tosevski, Vinko; Ulashchik, Egor; Trovato, Andrea; Cappella, Paolo
Abstract: Novel cell analyzers, including polychromatic flow cytometers and isotopical cytometry by time of flight (CyTOF) mass cytometers, enable simultaneous measurement of virtually bondless characteristics at the single‐cell level. BrdU assays for quantifying cellular proliferation are common but have several limitations, including the need for a DNA denaturation step and inability to simultaneously resolve multiple parameters and phenotypic complexity. Click chemistry reactions have become popular in the past decade, as they can resolve these issues. This protocol introduces a novel assay able to bridge flow cytometry and CyTOF analysis for active S‐phase determination in cell cycle applications, combining well‐established click chemistry with a novel iodo‐deoxyuridine (IdU) azide derivative and a cross‐reactive anti‐IdU antibody for detecting incorporated EdU during DNA synthesis. This method is preferred over traditional BrdU‐based assays for complex and multiparametric experiments. It provides a feasible cost‐effective approach for detecting ethynyl‐labeled nucleotides, with the advantage of combining flow and mass cytometry analyses. © 2017 by John Wiley & Sons, Inc.